Rafflesia zollingeriana Koord.: a Reinstatement - Lestari, Dewi; Mahyuni, Ridha (UIN Sunan Gunung Djati Bandung, 2021)
Rafflesia zollingeriana Koord. was one of Rafflesia that distributed in Java. Although it has been stated as a different species, R. zollingeriana is sometimes still regarded as a synonym of R. patma. In addition, there are several contradictions in description of R. zollingeriana.Â Therefore, further investigation is needed. This study attempts presents a full the description of the R. zollingeriana female flower. In this study, a full description of female flower of R. zollingeriana and pictures of important characters such as ramenta, annulus, perigone lobes, disc, processes, bractea are presented. This study is also compared the morphology of R. zollingeriana and R. patma, to confirm their differences in size, opening of diaphragm, blotches and warts pattern on perigone lobes and diaphragm, annulus, and ramenta.